Artificial Intelligence'S Role In Predictive Analytics For Patient Mental Health Care - Regina Putri, Frestiany; Ratri Sukmaningsih, Wahyu; Mukaromah, Maulina (LPPM Universitas Duta Bangsa Surakarta, 2024)
The aim of this study is to analyze the use of AI in mental health care using case-based reasoning methods, which generate treatment solution recommendations from previously occurring cases.